IMPROVING STUDENTS’ VOCABULARY IN DESCRIPTIVE TEXT USING WORD WALL MEDIA - Agustina, Anisa; Sada, Clarry; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is conducted on seventh grade B students of SMP Negeri 2 Rasau Jaya in academic year 2018/2019. The research is conducted to solve the students’ vocabulary problems about meaning and spelling in descriptive text. Classroom action research is used as the method of research. Individual vocabulary test, observation checklist and field note are used as the tools to collect the data. The research is done with two cycles. The result showed that the students’ understanding of meaning was improved by drawing and sticking pictures on word wall media. The students spelling were improved by rearranging the letters into words with right spelling. The students’ vocabulary improvement were proven by the students’ vocabulary test score and students’ behavior while learning vocabulary. The students’ mean score in understanding the meaning improved from 59.5 in cycle 1 to 83.6 in cycle 2. The students’ mean score of spelling improved from 65 in cycle 1 into 88.4 in cycle 2. Based on field note, the students were more active, enthusiastic and confident while learning English vocabulary in cycle 2. In conclusion, word wall media is recommended to be implemented by the English teacher to teach vocabulary in descriptive text. Keywords: Descriptive Text, Vocabulary, Word Wall Media